On the Approximated Solution of a Special Type of Nonlinear Third-Order Matrix Ordinary Differential Problem - Emilio Defez; Javier Ibáñez; José M. Alonso; Michael M. Tung; Teresa Real-Herráiz (Mathematics, 2021)
Matrix differential equations are at the heart of many science and engineering problems. In this paper, a procedure based on higher-order matrix splines is proposed to provide the approximated numerical solution of special nonlinear third-order matrix differential equations, having the form <semantics>Y(3)(x)=f(x,Y(x))</semantics>. Some numerical test problems are also included, whose solutions are computed by our method.